2015
DOI: 10.1016/j.jcmg.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Value of Exercise ECG for Risk Stratification in Suspected or Known CAD in the Era of Advanced Imaging Technologies

Abstract: Exercise stress electrocardiography (ExECG) is underutilized as the initial test modality in patients with interpretable electrocardiograms able to exercise. Although, stress myocardial imaging techniques provide valuable diagnostic and prognostic information, variables derived from ExECG can yield substantial data for risk stratification, either supplementary to imaging variables, or without concurrent imaging. In addition to exercise-induced ischemic ST depression, such markers as ST segment elevation in lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 102 publications
0
55
0
1
Order By: Relevance
“…Detrano et al [11] reported a sensitivity of 68% and specificity of 77% for the detection of coronary artery disease (CAD) in a meta-analysis that included over 24,000 patients and 22 years of research. Exercise-induced ST-segment depression is considered the strongest predictor of future cardiac events along with the duration of exercise and exercise capacity [12]. The Duke Treadmill Score (DTS) is a widely accepted tool used by many clinicians providing added prognostic information by combining exercise duration and ST changes and angina during exercise [13].…”
Section: Non-invasive Imaging Modalitiesmentioning
confidence: 99%
“…Detrano et al [11] reported a sensitivity of 68% and specificity of 77% for the detection of coronary artery disease (CAD) in a meta-analysis that included over 24,000 patients and 22 years of research. Exercise-induced ST-segment depression is considered the strongest predictor of future cardiac events along with the duration of exercise and exercise capacity [12]. The Duke Treadmill Score (DTS) is a widely accepted tool used by many clinicians providing added prognostic information by combining exercise duration and ST changes and angina during exercise [13].…”
Section: Non-invasive Imaging Modalitiesmentioning
confidence: 99%
“…At present, more than 10 million CAD imaging tests are being performed annually in the United States(11). Despite the high utilization and numerous options for noninvasive cardiac testing, uncertainty remains regarding the optimal testing strategies(12, 13). Multiple studies have investigated the value of ETT in comparison with non-invasive imaging modalities, however, a direct comparison of varying diagnostic strategies that employ non-invasive tests in isolation versus in succession to one another has to date not been assessed(9, 13).…”
Section: Introductionmentioning
confidence: 99%
“…7 Other prognostic variables derived from ExECG have proven useful for risk stratification. 8 Some findings of the study by Argulian et al 4 deserve mention and further discussion. Surprisingly, 81% (n = 922) of the patients in this cohort had stress echocardiography compared to only 19% (n = 218) who underwent SPECT MPI.…”
mentioning
confidence: 89%